Factors associated with the use of long-term contraceptive methods among women of reproductive age - Ayu Intania; Cucuk Kunang Sari (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: High population growth and unintended pregnancies remain significant public health challenges in developing countries. Long-Term Contraceptive Method (LTMC) are proven to be highly effective and cost-efficient in reducing maternal mortality, yet their utilization among women of reproductive age (WRA) remains low. Understanding the determinants of LTMC uptake is crucial for improving family planning programs. Purpose: To determine the factors associated with the use of long-term contraceptive methods among women of reproductive age. Method: A quantitative analytical study using a cross-sectional approach was conducted on 99 respondents selected using consecutive sampling techniques. Data were collected using a questionnaire and analyzed using the Chi-square test. Results: The results showed significant associations between knowledge (p=0.011), attitude (p=0.003), husband's support (p=0.001), and LARC utilization. Conclusion: Knowledge, attitude, and husband's support were significantly associated with LARC utilization among women of reproductive age.